Consumption motivation of limited edition product in reselling open market - Woodong Kim; Bo-Young Kim (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Recently, the phenomenon of purchasing limited edition products has been spreading rapidly in the reselling open market. As various technologies are introduced in the era of the fourth industrial revolution, platform-centered digital distribution has become popular and consumers buy limited edition products as a reflection of their various access behaviors to satisfy their social needs for reselling and not out of mere curiosity or personal preference. Accordingly, this study includes a survey conducted among 564 consumers of limited edition products who were leading the consumer-centered reselling open markets in Korea. Specifically, five factors of limited edition products consumption motivation - functional, emotional, social, epistemic, and economic - are defined, and how these factors affect the continuous consumption attitudes of consumers with such active consumption attitudes as a medium is considered. The analysis result shows that emotional factors are not significant as a motivation factor to limited product consumption while economic factors had a significant effect on the behavior of continued resale product consumption. This result clearly indicates that while consumers sometimes purchased limited edition products merely out of functional, social, and epistemic motivation, acquiring economic value through reselling in the customer to customer open market was also an important consumption motivation.
Keywords: 650; active customer; consumption motivation; innovative behavior; limited edition product; reselling open market